2020
DOI: 10.21203/rs.3.rs-112660/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with survival in Adult Patients with Traumatic Arrest: A Retrospective Cohort Study from US Trauma Centers

Abstract: Background: Traumatic arrests (TA) increasingly affect young adults worldwide with low reported survival rates. This study examines factors associated with survival (to hospital discharge) in traumatic arrests transported to US trauma centers. Methods: This retrospective cohort study used the US National Trauma Databank 2015 dataset and included patients who presented to trauma centers with “no signs of life”. Univariate and bivariate analyses were done. Factors associated with survival were identified using m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We are aware of several studies showing that prehospital AAM is not beneficial for improving mortality in trauma patients. 2,13,18 Tsur et al 19 showed prehospital definitive airway did not benefit the improvement of survival. However, the survival rates in their series were 77.6% for secured airway patients and 78.0% for failed definitive airway patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are aware of several studies showing that prehospital AAM is not beneficial for improving mortality in trauma patients. 2,13,18 Tsur et al 19 showed prehospital definitive airway did not benefit the improvement of survival. However, the survival rates in their series were 77.6% for secured airway patients and 78.0% for failed definitive airway patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we undertook a subgroup analysis using conditional logistic regression analysis based on body regions where the severe injury occurred, as physiological impact could differ depending on the injury site (severe head injury, severe torso (chest or abdominal) injury, severe extremity/spine injury). 13 Severe injury was defined as AIS ≥ 3. The same analyses were applied for each respective subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation